International Protection of Intellectual Property - Grossman, Gene M; Lai, Edwin L.-C (American Economic Review, 2004)
We study the incentives that governments have to protect intellectual property in a trading world economy. We consider a world economy with ongoing innovation in two countries that differ in market size and in their capacity for innovation. After describing the determination of national patent policies in a noncooperative regime of patent protection, we ask, “Why is intellectual property better protected in the North than in the South?” We also study international patent agreements by deriving the properties of an efficient global regime of patent protection and asking whether harmonization of patent policies is necessary or sufficient for global efficiency.